LACE Index to Predict the High Risk of 30-Day Readmission in Patients With Acute Myocardial Infarction at a University Affiliated Hospital - Rajaguru, Vasuki; Kim, Tae Hyun; Han, Whiejong; Shin, Jaeyong; Lee, Sang Gyu (Frontiers in Cardiovascular Medicine, 2022)
Background: The LACE index (length of stay, acuity of admission, comorbidity index, and emergency room visit in the past 6 months) has been used to predict the risk of 30-day readmission after hospital discharge in both medical and surgical patients. This study aims to utilize the LACE index to predict the risk of 30-day readmission among patients with AMI in South Korea. Methods: This was a retrospective study. LACE index scores were calculated for patients admitted with AMI between 2015 and 2019. Data were extracted from the hospital's electronic medical record, including patient demographic data, and clinical and laboratory findings during the index of admission. The multivariate logistic regression was performed to determine the association between potential risk factors and 30-day readmission. The risk prediction ability of the LACE index and 30-day readmission were analyzed by receiver operator characteristic curves with C-statistic. Results: Of the 3,607 patients included in the study, 5.7% (205) were readmitted within 30days of discharge from the hospital. The adjusted odds ratio based on logistic regression of all baseline variables showed a statistically significant association with the LACE score and revealed an increased risk of readmission within 30 days of hospital discharge. However, patients with high LACE scores (≥10) had a significantly higher rate of emergency revisits within 30 days from the index discharge than those with low LACE scores. Despite this, analysis of the receiver operating characteristic curve indicated that the LACE index had a favorable discrimination ability (C-statistic = 0.75) to predict the risk of the 30-day readmission. Conclusion: The LACE index demonstrated the good discrimination power to predict the risk of 30-day readmissions for hospitalized patients with AMI. Future work is to be focused on additional factors to predict the risk of 30-day readmissions; they should be considered to improve the model performance of the LACE index with other acute conditions by using National Health Insurance Service (NHIS) claims data.